X-ray cavities in TNG-Cluster: AGN phenomena in the full cosmological context - Prunier, Marine; Hlavacek-Larrondo, Julie; Pillepich, Annalisa; Lehle, Katrin; Nelson, Dylan (Monthly notices of the Royal Astronomical Society, 2025)
Active galactic nuclei (AGNs) feedback from supermassive black holes (SMBHs) at the centres of galaxy clusters plays a key role in regulating star formation and shaping the intracluster medium, often manifesting through prominent X-ray cavities embedded in the cluster’s hot atmosphere. Here we show that X-ray cavities arise naturally due to AGN feedback in TNG-Cluster. This is a new suite of magnetohydrodynamic cosmological simulations of galaxy formation and evolution, and hence of galaxy clusters, whereby cold dark matter, baryon dynamics, galactic astrophysics, and magnetic fields are evolved together consistently. We construct mock Chandra X-ray observations of the central regions of the 352 simulated clusters at z = 0 and find that $\sim$39 per cent contain X-ray cavities. Identified X-ray cavities vary in configuration with some still attached to their SMBH, while others have buoyantly risen. Their size ranges from a few to several tens of kpc. TNG-Cluster X-ray cavities are underdense compared to the surrounding halo and filled with hot gas ($\sim 10^8$ K); 25 per cent of them are surrounded by an X-ray bright and compressed rim associated with a weak shock (Mach number $\sim$1.5). Clusters exhibiting X-ray cavities are preferentially strong or weak cool-cores, are dynamically relaxed, and host SMBHs accreting at low Eddington rates. We show that TNG-Cluster X-ray cavities originate from episodic, wind-like energy injections from central AGN. Our results illustrate the existence and diversity of X-ray cavities simulated in state-of-the-art models within realistic cosmological environments and show that these can form without necessarily invoking bipolar, collimated, or relativistic jets.
Gesehen am 07.11.2025
Online veröffentlicht: 12. Dezember 2024